PENGARUH DIGITAL MARKETING TERHADAP KEPUTUSAN PEMBELIAN SR 12 PADA DISTRIBUTOR SUKOHARJO - Wahayuningtias, Citra; Wagiyo, Wagiyo; Arohman, Arohman; Pranoto, Gusti Adi (Jurnal Signaling, 2023)
A purchase decision is a decision made by a customer based on a set of identified issues, then accompanied by a search for information related to the customer's needs. This study was conducted to determine whether digital marketing influences the decision to purchase SR12 products from a Sukoharjo distributor. The subjects of this study are SR12 customers at distributor Sukoharjo who have used SR12 products. The sample used was 96 respondents. Sampling using probability sampling technique. This study uses quantitative research method, the data collection is done by questionnaire. Data analysis using simple linear regression, t-test and correlation coefficient. The research results conclude that there is an influence of digital marketing on the decision to buy SR12 products at distributor Sukoharjo, which is determined by the positive influence between tcount ttable.